Peran Tokoh Masyarakat Dalam Upaya Mencegah Pergaulan Toxic Remaja Di Kecamatan Bintang Kabupaten Aceh Tengah - Zita Gustina; Arifin Zain; Juli Andriyani (Yayasan Madinah Al-Aziziyah, 2026)
Toxic socialization among the younger generation has become an increasingly concerning phenomenon, characterized by various forms of deviant behavior, including the widespread practice of online gambling, offensive language, ilegal street racing, theft, and bullying. Addressing juvenile delinquency has largely been examined through the perspectives of family parenting, the role of schools, and formal law enforcement, while the role of community leaders within the Gayo socio-cultural context remains understudied. This study aims to examine the role of community leaders in preventing toxic socialization among youth and to identify the challenges they encounter in carrying out these efforts in Bintang District, Central Aceh Regency. The research was conducted in Linung Bulen I Village and Wakil Jalil Village using a qualitative approach with a descriptive research method. Data were collected through observation, in-depth interviews, and documentation involving 12 informants consisting of community leaders and youth, who were selected using a purposive sampling technique. The findings reveal that community leaders perform their social control function through four dimensions: normative-educational, humanistic-persuasive, facilitative roles through youth empowerment, and repressive roles based on customary sanctions. However, these efforts face significant structural and cultural challenges, including the defensive attitudes of youth, weak parental supervision, the declining sense of collective responsibility embedded in Gayo customary values, as well as the temporary nature of advice and the problem of one-way communication from community leaders to adolescents. Overall, the role of community leaders has been functioning but remains sub-optimal because the preventive approach is still dominated by situational verbal appeals and inconsistent programs, while lacking support from active family supervision and binding written village regulations (qanun).